1979
DOI: 10.1007/bf01008658
|View full text |Cite
|
Sign up to set email alerts
|

Influence of levamisole on the capacity of neutrophil granulocytes for ingestion and for the reduction of nitrobluetetrazolium

Abstract: With the aid of a modification of the NBT test it has been shown in in vitro and in vivo studies that levamisole does not affect the NBT reduction capacity of neutrophil granulocytes. The increased NBT positivity of these cells under the influence of levamisol is due to stimulation of ingestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It means that neither the INT reductase activity nor the superoxide generation in normal PMNs during phagocytosis of zymosan particles were influenced by levamisole. ESCHENBACK et al [35] also found that levamisole did not affect NBT reduction by normal PMNs but it was able to stimulate the ingestion of heat-killed staphylococci coated by NBT. Thus it seems that levamisole has probably a different effect on NBT or INT reduction capacity of normal and SLE polymorphs.…”
Section: Discussionmentioning
confidence: 93%
“…It means that neither the INT reductase activity nor the superoxide generation in normal PMNs during phagocytosis of zymosan particles were influenced by levamisole. ESCHENBACK et al [35] also found that levamisole did not affect NBT reduction by normal PMNs but it was able to stimulate the ingestion of heat-killed staphylococci coated by NBT. Thus it seems that levamisole has probably a different effect on NBT or INT reduction capacity of normal and SLE polymorphs.…”
Section: Discussionmentioning
confidence: 93%